1970
DOI: 10.1063/1.1659222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Shape on the Infrared Absorption Spectra of Barium Titanate and Strontium Titanate Powders

Abstract: Effects of particle size and particle shape have been studied in the infrared absorption spectra of BaTiO3 and SrTiO3 powders to determine whether previously developed methods to treat such effects are applicable to crystals having high dielectric constant and ``soft'' lattice modes. The spectrum of both materials exhibits three absorption bands (BaTiO3: 545, 400, and 180 cm−1; SrTiO3: 605, 400, and 175 cm−1) that are considerably removed from the TO-mode frequencies computed from bulk single-crystal reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…al. have studied the effects of particle size and particle shape in the infra-red spectra of barium and scrontium titanate powders and showed that for small crystals, especially the fine powders, the departure from bulk mode frequencies may become quite large [13]. In this work, the different particle size and morphology of potassium hexatitanates (as seen in SEM results) were obtained from the different preparative conditions.…”
mentioning
confidence: 89%
“…al. have studied the effects of particle size and particle shape in the infra-red spectra of barium and scrontium titanate powders and showed that for small crystals, especially the fine powders, the departure from bulk mode frequencies may become quite large [13]. In this work, the different particle size and morphology of potassium hexatitanates (as seen in SEM results) were obtained from the different preparative conditions.…”
mentioning
confidence: 89%
“…l a . The high frequency part of the spectrum is due to Last [3] and the extension t.0 frequencies below 300 em-1 is due to Luxon et al [4]. Since the observed absorption maxima do not agree with the Frohlich frequencies, we have calculated the extinction cross section from equation (8).…”
Section: Analysis Of Infrared Absorption Datamentioning
confidence: 99%
“…As a result the Raman and also IR lines in ceramics resulting from the mode mixing and long range electrostatic force effects are relatively broader than that found in single crystals. The phonon frequencies also shift remarkably to higher/lower values depending upon the finite size of the powder grains and due to depelarization fields [27]. This can be the reason for the shifting of frequencies between the Raman and IR measurements.…”
Section: Introductionmentioning
confidence: 96%